Setting priorities for people with intellectual disability/intellectual developmental disorders across the lifespan: a call to action by the World Psychiatric Association. (August 2021) - Roy, Ashok; Courtenay, Ken; Odiyoor, Mahesh; Walsh, Patricia; Keane, Sarah; Biswas, Asit; Marston, Geoff; Thirulokachandran, Suchithra; Munir, Kerim
Abstract : People with DSM-5 intellectual disability/intellectual developmental disorder (ID/IDD) or ICD-11 disorders of intellectual development (DID) have multiple healthcare needs, but in many countries these needs are neither recognised nor managed effectively. This paper discusses the negative impact that stigma, discrimination and social exclusion have on the identification and care of persons with ID/IDD in low- and middle-income countries (LMICs). It also reviews different models of care for children, adolescents and adults. In discussing some initiatives in LMICs the emphasis is on early diagnosis, with success in providing locally sourced care for affected people and their families. This is where the medical, social and rights-based models of care intersect and is a premise of the person-centred biopsychosocial framework of the World Psychiatric Association's Presidential Action Plan 2020–2023. The plan invites psychiatrists to take a lead in changing the culture of care, as well as medical education, clinical training and research, with a renewed emphasis on workforce integration and service development in terms of community-based rehabilitation strategies.